Fusion peptide of HIV-1 as a site of vulnerability to neutralizing antibody - Kong, Rui (Science, 2016)
The HIV-1 fusion peptide, comprising 15 to 20 hydrophobic residues at the N terminus of the Env-gp41 subunit, is a critical component of the virus-cell entry machinery. Here, we report the identification of a neutralizing antibody, N123-VRC34.01, which targets the fusion peptide and blocks viral entry by inhibiting conformational changes in gp120 and gp41 subunits of Env required for entry. Crystal structures of N123-VRC34.01 liganded to the fusion peptide, and to the full Env trimer, revealed an epitope consisting of the N-terminal eight residues of the gp41 fusion peptide and glycan N88 of gp120, and molecular dynamics showed that the N-terminal portion of the fusion peptide can be solvent-exposed. These results reveal the fusion peptide to be a neutralizing antibody epitope and thus a target for vaccine design.